HOW AI IS RESHAPING LANGUAGE LEARNING (International Conference on Modern Science and Scientific Studies, 2025)
The view of language learning is undergoing a dramatic transformation, driven by the rapid advancements in artificial intelligence (AI). Once this process was managed by textbooks, classrooms, and human instructors, language acquisition is increasingly being influenced by AI-powered tools and platforms. This article explores the profound ways in which AI is reshaping language learning, examining the benefits, challenges, and potential future directions of this technological evolution.